Pelatihan dan Pendampingan Aplikasi Accurate untuk Meningkatkan Literasi Digital Akuntansi Guru SMK di Jakarta Utara - Yuana Jatu Nilawati; Khomsiyah Khomsiyah; Asep Hermawan (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
This community service program aims to enhance the digital accounting literacy of vocational high school (SMK) teachers in North Jakarta through a training and mentoring program using the Accurate accounting application. The main issue addressed is the limited competence of teachers in understanding and applying technology-based accounting cycles, which requires structured intervention through training, hands-on practice, and mentoring activities. This program is significant in supporting the improvement of vocational education quality and preparing students for the demands of a digitally driven workforce. The program employed a mixed-methods approach with a one-group pretest-posttest design. Data were collected from 20 SMK teachers through pretests and posttests, observations, and participant discussions, and analyzed using descriptive quantitative and qualitative thematic approaches. The results show an increase in participants’ understanding, with the average score rising from 55 to 82. In addition, participants demonstrated improved skills in using the Accurate application to prepare financial statements independently. These findings indicate that practice-based training combined with mentoring contributes to improving teachers’ competencies and the quality of accounting learning. It is recommended that this program be expanded through advanced training, broader participant involvement, and integration into the vocational school curriculum to support the digital transformation of vocational education.